2022
DOI: 10.3390/cells11172674
|View full text |Cite
|
Sign up to set email alerts
|

TcpC Inhibits M1 but Promotes M2 Macrophage Polarization via Regulation of the MAPK/NF-κB and Akt/STAT6 Pathways in Urinary Tract Infection

Abstract: TcpC is a multifunctional virulence factor of Uropathogenic Escherichia coli (UPEC). Macrophages can differentiate into two different subsets M1 and M2 that play distinct roles in anti-infection immunity. Here, we investigate the influence of TcpC on M1/M2 polarization and the potential mechanisms. Our data showed that M1 markers CD86 and iNOS were significantly inhibited, while the M2 markers CD163, CD206 and Arg-1 were enhanced in macrophages in kidneys from the TcpC-secreting wild-type CFT073 (CFT073wt)-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 66 publications
0
20
0
Order By: Relevance
“…Two main signaling pathways, the Akt/mTORC/LXR pathway and the JAK/STAT6 pathway, are two major signaling pathway for M2 polarization. (Bi et al, 2019;Fang et al, 2022). Besides, Th2 cell-secreted molecules, such as IL-4, can also induce the differentiation of macrophages toward M2 phenotype, thereby alleviating inflammation by inhibiting the mitogen-activated protein kinase signaling pathway (Zhao et al, 2016).…”
Section: Macrophages and Inflammation In Atherosclerosismentioning
confidence: 99%
“…Two main signaling pathways, the Akt/mTORC/LXR pathway and the JAK/STAT6 pathway, are two major signaling pathway for M2 polarization. (Bi et al, 2019;Fang et al, 2022). Besides, Th2 cell-secreted molecules, such as IL-4, can also induce the differentiation of macrophages toward M2 phenotype, thereby alleviating inflammation by inhibiting the mitogen-activated protein kinase signaling pathway (Zhao et al, 2016).…”
Section: Macrophages and Inflammation In Atherosclerosismentioning
confidence: 99%
“…Subsequent trans-regulation and cis-regulation analyses were carried out to further understand the signaling pathways and molecular networks involved in the differentially expressed LncRNAs of MWCNTs- and PBS-treated THP-1 Mφ cells. From the top 20 KEGG pathways (Figures S8A,B and S9A,B) and molecular networks (Figures S8C and S9C) in trans-regulation and cis-regulation, we found M2-related signaling pathways including the TNF pathway, NF-κB pathway, TGF-β pathway, and MAPK pathway were significantly highlighted. …”
Section: Resultsmentioning
confidence: 94%
“…TNF‐α plays an indispensable role in regulating immune cells and inflammatory responses, and TNF‐α dysregulation can cause inflammatory responses such as fever, edema and tissue damage [45] . In addition, CD86 is often used as a membrane molecular marker of macrophage M1 subtype [46] . In this study, we firstly investigated the effect of dendrocandin U on the production of iNOS, TNF‐α and CD86, and it was found that dendrocandin U could inhibit the expression or secretion of iNOS, TNF‐α and CD86 at 20 μM (Figure 5A, B, C).…”
Section: Discussionmentioning
confidence: 98%
“…[45] In addition, CD86 is often used as a membrane molecular marker of macrophage M1 subtype. [46] In this study, we firstly investigated the effect of dendrocandin U on the production of iNOS, TNF-α and CD86, and it was found that dendrocandin U could inhibit the expression or secretion of iNOS, TNF-α and CD86 at 20 μM (Figure 5A, B, C). These results suggest that dendrocandin U plays an anti-inflammatory role by inhibiting the polarization of MHÀ S towards M1.…”
Section: Discussionmentioning
confidence: 99%